The Politics of Race in Panama : Afro-Hispanic and West Indian Literary Discourses of Contention - Watson, Sonja Stephenson (Book collections on Project MUSE., 2014)
Black Panamanians, unlike other Aftro-Latin communities, have traditionally separated themselves based on ancestral heritage: on one hand are those whose ancestors were slaves during the colonial period; on the other are those whose families arrived from the West Indies to help build the Panama Railroad and Canal. In this book, Watson assesses how Panamanian literature represents this historical and continuing tension.